Patient centricity in pharmacovigilance: how we can elevate a patient’s voice - Pareschi, Raphael Elmadjian (Henry Stewart Talks, 2025)
Importance of pharmacovigilance (PV), The drug discovery process, WHO global patient safety action plan, 2021 to 2030, Elevating a patient’s voice and patient engagement in healthcare, Risk management in post marketing, Reporting Adverse Drug Reactions (ADRs)